Reading, equivalence, and recombination of units: A replication with students with different learning histories - Melchiori, L. E.; de Souza, D. G.; de Rose, J. C. (Journal Appl Behav Anal, 2000)
First graders, preschoolers, special education students, and adults received a reading program in which they learned to match printed to dictated words and to construct (copy) printed words. The students not only learned to match the training words but also learned to read them. In addition, most of the students learned to read new words that involved recombinations of the syllables of the training words. The results replicate and extend the generality of a prior analysis of a reading program based on stimulus equivalence and recombination of units.
Keywords: reading; stimulus equivalence; recombinatory generalization; exclusion; matching to sample; nonreading adults